INITIAL DATA ON THE COMPOSITION OF ANTS (Hymenoptera: Formicidae) IN THUONG TIEN NATURE RESERVE, HOA BINH PROVINCE - Bao Thanh, Le; Xuan Truong, Bui (Journal of Forestry Science and Technology, 2017)
Thuong Tien Nature reserve has high level of biodiversity. However, insect is one of the least study groups compared to other groups of animals in the reserve. In this study ant specimens were collected by using line-transect and point methods in Thuong Tien Nature reserve. Consequently, the researchers has initially identified 34 species of ants in 04 subfamilies (Dolichoderinae, Formicinae, Myrmicinae, and Ponerinae), and 23 genus. Of the 34 species, there are 10 ones that has been only determined for genus. According to the research results, Crematogaster and Leptothorax are the genus that have the largest number of species of 03 each. Technomyrmex, Plagiolepis, Aphaenogaster, Monomorium, Pheidole, Tetramorium, and Leptogenys have 2 species each. The rest ones have 01 species each. The subfamily of Myrmicinae predominates in the number of both genus and species (12 genus and 20 species). The subfamilies of Ponerinae and Formicinae have 04 genus and 05 species for each. The subfamily of Dolichoderinae has 03 genus and 04 species. In the residential habitats, agricultural plants have the highest species rate and Margalef index (d). Bamboo and regenerative forest habitats have lower species rate and Margalef index (d). The lowest species rate and Margalef index (d) are of the habitat of evergreen forest of high trees.